Physicochemical properties of bone marrow mesenchymal stem cells encapsulated in microcapsules combined with calcium phosphate cement and their ectopic bone formation - Yuan, Yafei; Shen, Lipei; Liu, Tiankun; He, Lin; Meng, Dan; Jiang, Qingsong (Frontiers in Bioengineering and Biotechnology, 2022)
Calcium phosphate bone cement (CPC) serves as an excellent scaffold material for bone tissue engineering owing to its good biocompatibility, injectability, self-setting property and three-dimensional porous structure. However, its clinical use is limited due to the cytotoxic effect of its setting reaction on cells and difficulties in degradation into bone. In this study, bone marrow mesenchymal stem cells (BMSCs) were encapsulated in alginate chitosan alginate (ACA) microcapsules and compounded with calcium phosphate bone cement. Changes in the compressive strength, porosity, injectability and collapsibility of CPC at different volume ratios of microcapsules were evaluated. At a 40% volume ratio of microcapsules, the composite scaffold displayed high porosity and injectability with good collapsibility and compressive strength. Cell live/dead double staining, Cell Counting Kit-8 (CCK-8) assays and scanning electron microscopy were used to detect the viability, proliferation and adhesion of cells after cell microcapsules were combined with CPC. The results revealed that cells protected by microcapsules proliferated and adhered better than those that were directly combined with CPC paste, and cell microcapsules could effectively form macropores in scaffold material. The composite was subsequently implanted subcutaneously on the backs of nude mice, and ectopic osteogenesis of the scaffold was detected via haematoxylin-eosin (H&E), Masson’s trichrome and Goldner’s trichrome staining. CPC clearly displayed better new bone formation function and degradability after addition of pure microcapsules and cell microcapsules. Furthermore, the cell microcapsule treatment group showed greater osteogenesis than the pure microcapsule group. Collectively, these results indicate that BMSCs encapsulated in ACA microcapsules combined with CPC composite scaffolds have good application prospects as bone tissue engineering materials.